Fatores relacionados ao baixo desempenho cognitivo da pessoa idosa em seguimento ambulatorial - Machado, Alice Irene Sena (Universidade Federal de São Carlos)
Introduction: The current brazilian context shows that the growth of the population aged 60 years or older occurs concurrently with high rates of chronic diseases, hospitalizations, and declines in physical and cognitive capacities. This leads to a significant increase in healthcare costs, given that hospitalization rates among older adults are higher and their length of stay is longer than in other age groups. Dementia, a cognitive decline that affects memory, thinking, and the ability to perform daily activities, is one of the main causes of disability among older adults. In this sense, the major challenge for health systems is to ensure comprehensive care for users aged 60 years or older. Objective: To characterize the sociodemographic and clinical profile of older adults followed at the Gerontology Outpatient Clinic of HU-UFSCar and to examine the factors related to their low cognitive performance. Method: A quantitative, cross-sectional approach in which individuals aged sixty years or older were treated at the respective Outpatient Clinic. Data collection took place from October 2023 to April 2024 through the application of a protocol that included assessment of frailty using the Clinical-Functional Vulnerability Index; cognitive performance using the 10-Point Cognitive Screener; degree of dependence in basic activities using the Katz Index and in instrumental activities using the Lawton Scale; and evaluation of depressive symptoms using the 15-item version of the Geriatric Depression Scale. Pearson’s correlation was used to verify the relationship between the variable low cognitive performance and age in years, educational level, number of comorbidities, number of medications, clinical-functional vulnerability, dependence in basic and instrumental activities of daily living, and the presence of depressive symptoms. All ethical aspects were respected. Results: A total of 92 older adults were assessed, mostly female (64.1%), with a mean age of 78.7 years (±8.7), self-declared White (57.3%), and non-practicing religious (51.1%). The mean educational level was 5.6 years (±4.5), with a higher prevalence of individuals with up to 4 years of schooling (58.7%). Regarding marital status, half of the sample were married/living with a partner (50.55%). Concerning functional capacity, 62% were partially dependent for instrumental dependence, 38% for functional dependence, 57.4% were highly vulnerable, and they presented multimorbidities (69.57%). Older adults with low cognitive performance represented 79.3% of the sample and had a mean age of 80.27%. Conclusion: Low cognitive performance was associated with age (p<0.01) and with high dependence for basic activities of daily living (p=0.01). The increased risk of subsequent cognitive impairment, age, and limitations in performing basic life activities suggest prioritizing attention to the impact of age-related changes in health status on cognition and related factors.
Factors associated with low cognitive performance in older adults receiving outpatient follow-up
Keywords: Ambulatório hospitalar; Assistência ambulatorial; Assistência integral à saúde; Idoso; Saúde do idoso; Outpatient clinic; Outpatient care; Comprehensive healthcare; Older adult; Older adults’ health; CIENCIAS DA SAUDE; 3. Saúde e Bem-Estar